Assessing the health impact of transnational corporations: its importance and a framework. Issue 1 (December 2016) - Baum, Frances; Sanders, David; Fisher, Matt; Anaf, Julia; Freudenberg, Nicholas; Friel, Sharon; Labonté, Ronald; London, Leslie; Monteiro, Carlos; Scott-Samuel, Alex; Sen, Amit
Abstract Background The adverse health and equity impacts of transnational corporations' (TNCs) practices have become central public health concerns as TNCs increasingly dominate global trade and investment and shape national economies. Despite this, methodologies have been lacking with which to study the health equity impacts of individual corporations and thus to inform actions to mitigate or reverse negative and increase positive impacts. Methods This paper reports on a framework designed to conduct corporate health impact assessment (CHIA), developed at a meeting held at the Rockefeller Foundation Bellagio Center in May 2015. Results On the basis of the deliberations at the meeting it was recommended that the CHIA should be based on ex post assessment and follow the standard HIA steps of screening, scoping, identification, assessment, decision-making and recommendations. A framework to conduct the CHIA was developed and designed to be applied to a TNC's practices internationally, and within countries to enable comparison of practices and health impacts in different settings. The meeting participants proposed that impacts should be assessed according to the TNC's global and national operating context; its organisational structure, political and business practices (including the type, distribution and marketing of its products); and workforce and working conditions, social factors, the environment, consumption patterns, and economic conditions within countries. Conclusion We anticipate that the results of the CHIA will be used by civil society for capacity building and advocacy purposes, by governments to inform regulatory decision-making, and by TNCs to lessen their negative health impacts on health and fulfil commitments made to corporate social responsibility.